Auditoría financiera a la cooperativa de ahorro y crédito Ambato Ltda. ubicada en el cantón Saquisilí, provincia de Cotopaxi, en el período octubre – diciembre del 2012 - Jacho Vilcaguano, Rosa Maricela (2014)
The Financial Audit was completed based on the standard practice of Financial Management, based on Generally Accepted Auditing Standards NAGAS, same as that used in the Savings and Credit Cooperative Ltd. located in Ambato Canton Saquisili to detect the problems and shortcomings within the entity and to develop conclusions and recommendations to improve the area audited. The audit procedures and techniques that are applied to plan activities and to determine compliance with the principles and accepted accounting standards , aimed at finding problems and weaknesses in the audited accounts , allowing to analyze in order to optimize them for smooth running of the Cooperative. One of the main reasons to apply a financial audit, is to know the degree of fulfillment of corporate objectives, in which it will issue a report in which all consist sufficient competent evidence to support the information so when issuing that report to top management with their observations and recommendations which shall apply within the institution for better economic management and financial resources of the cooperative.